Advantages and Limitations of Leap Motion from a Developers', Physical Therapists', and Patients' Perspective - Gamboa, Edwin; Serrato, Andres; Castro, Juan; Toro, Diana; Trujillo, Maria (Methods of Information in Medicine, 2020)
Background Physical rehabilitation exergames (PREGs) are suitable for motivating patients toward completing treatments. Leap Motion (LM) is a motion sensor that may be useful for developing PREGs targeted at hands and fingers rehabilitation. Therefore, knowing the advantages and limitations of LM is relevant to understand under which conditions this sensor may be suitable.Objective In this article, we present a qualitative study to identify the main advantages and limitations of LM for PREGs.Methods We collect data using interviews with a group of PREGs developers, physical therapy experts, and patients. We employ the thematic analysis method to analyze the collected data.Results We found that the advantages and limitations of LM are related to (1) the role as PREG development tool that enables hand movements detection, (2) the capability to be a mobile and easy-to-use capturing technology, and (3) the contribution to add value in rehabilitation therapy by motivating physical therapists and patients to use PREGs.Conclusion The analysis shows that LM is a suitable and cost-effective solution for developing usable PREGs for some hand and finger rehabilitation movements with a moderate development effort. However, the development maturity of LM poses limitations related to reliability and robustness, preventing the use of LM as a standalone physical rehabilitation tool. Our findings serve as guidelines for developers and physical therapists during the development and use of PREGs targeted at hands and fingers, guiding the decision-making process during feasibility analysis and design stages.
Keywords: Leap Motion advantages and limitations; physical rehabilitation exergames development; hand and finger movements; hands rehabilitation support